The Emergence of African Authors in the Comic Field of French-speaking Europe (1978-2016) - (:unkn) unknown (My University, 2017)
This research examines the conditions of possibilities within and the routes of entry of the African authors into the comic field of the French-speaking Europe. The dissertation employs a sociological approach by making, firstly, an institutional analysis of the conditions of production, circulation and reception, as well as the sociability in the local contexts, in particular in the French-speaking countries of sub-Saharan Africa. The examination of the modalities of publication in the edition or in the press, of the associations of authors, festivals and other promotional initiatives, and of the possibilities offered by associations and institutions, shows that local authors have to realize their artistic vocation and their professional projects in poorly organized and unfavourable environments. Of course, this state of things requires agents to exercise their greater or lesser skill in adapting to it and making it play to the advantage of their professional career, but it also prompts a number of authors to consider the publication in the European field as the goal towards which to focus their efforts and strategies. The general problem of entry is the angle of attack of the second part, which draws on Pierre Bourdieu’s theory of fields to analyse the trajectories of the few African comics authors who managed to achieve a certain legitimation in European environments, namely Congolese Barly Baruti and Pat Masioni and the Ivorian Marguerite Abouet, as well as some other significant paths. The notions of habitus, strategy, periphery, autonomy and heteronomy, but also antinomy have helped to illuminate these paths. The theory of fields, which emphasizes the social conditions relating to the creation, circulation and consumption of symbolic goods and the institutions involved in the "mise en act" of the artistic-cultural object, in order to understand the position in the society of reference, was instrumental in understanding the importance of several
Keywords: African Research